Gene–Environment Interactions and Intermediate Phenotypes: Early Trauma and Depression - Hornung, Orla; Heim, Christine (Frontiers in Endocrinology, 2014)
This review focuses on current research developments in the study of Gene x ELS interactions and depression. It serves as a snapshot report of the most recent findings in this dynamic and complex field of research. After several years of investigating and characterizing the specific role of early life stress within the pathogenesis of depression and linking these findings to neurobiological changes of the brain, especially the stress response system, the latest findings highlight the role of genetic factors that increase vulnerability or, likewise, promote resilience to depression after childhood trauma. Considering intermediate phenotypes has further increased our understanding of the complex relationship between early trauma and depression. Recent findings with regard to epigenetic changes resulting from adverse environmental events during childhood promote current aspirations to identify specific target areas for prevention and treatment schemes regarding the long-term impact of early life stress. Taken together, latest findings have underscored the essential role of genotypes and epigenetic processes within the development of depression after childhood trauma, thereby building the basis for future research and clinical interventions.